Socioeconomic factors' effect on return to work after first stroke. (21st July 2016) - Glader, E.‐L.; Jonsson, B.; Norrving, B.; Eriksson, M.
Abstract : Objective: The objective of this nationwide study was to analyze how functional status and socioeconomic status affect return to work (RTW) among younger patients with first‐time stroke in a Sweden. Material and methods: This register‐based cohort study included employed patients aged 25–55 with first‐time stroke between 2008 and 2011 and primary outcome was RTW within 1 year after stroke. Data regarding functional status and employment status were retrieved from the Swedish Stroke Register, Riksstroke, and socioeconomic data (income, education, and country of birth) from Statistics Sweden. Results: We included 2539 patients who had answered the question on RTW, and 1880 (74.0%) had RTW within 12 months. Patients with low income (69.9% in lowest income group vs 79.9% in highest group, P <.001), patients born in countries outside the Nordic countries (Sweden 75.5%, Nordic countries 74.3%, European countries 61.7%, other countries 57.3%, P <.001), and the youngest patients (25–34, 63.1%; 35–44, 75.9%; 45–55, 74.3%; P =.008) were less likely to RTW. Pain, low mood, and answering the questionnaire with help were more common in low socioeconomic groups, and when adjusting for these variables, together with age and sex, income and country of birth were no longer independent predictors for RTW. Conclusion: Patients with low socioeconomic status less often RTW 1 year after stroke.Impaired functional status after stroke is more common in patients with lower socioeconomic status and mediates socioeconomic differences in RTW. Improvement of functional status should be targeted to facilitate RTW among stroke patients with low socioeconomic status.